Trolox induces inhibition of cell proliferation and apoptosis in human colon cancer cells - Li-Guang Yang; Xiang-An Tian; Xiao-Yan Li; Jian-Guo Huang; Nai-Qing Liu; Qin-Li Sun (Bangladesh Pharmacological Society, 2015)
In the present study, the effect of trolox on human colon cancer cell lines was investigated. The results revealed that trolox treatment caused inhibition of cell growth in T84 and HCT-15 colon cancer cell lines in a dose-dependent manner. The inhibition was significant at 50 µM of trolox after 48 hours in both cell lines. Trolox treatment promoted expression of p38 and inhibited expression of survivin and Akt. It also induced cleavage of PARP and caspase-3 and ultimately induced apoptosis in T84 and HCT-15 cells. The tumor growth was inhibited significantly in the xenotransplanted mice on treatment with trolox compared to the control group. Since trolox treatment exhibits inhibitory effect on the proliferation of colon cancer cells and inhibits tumor growth in vivo therefore, can be of therapeutic importance for the treatment of colon cancer.